Unlocking Potential: Knowledge Management Maturity Assessment And The Imperative Of Integrated People-Process-Technology - Moh Muzammil; Meirani Harsasi; Faridah Iriani (EKOMBIS REVIEW: Jurnal Ilmiah Ekonomi dan Bisnis, 2026)
This study aimed to ascertain the Knowledge Management (KM) maturity level at a technology-driven, open and distance education university in Indonesia. KMM was assessed across three core indicators: people, process, and technology. To capture respondent perceptions, each indicator was delineated into five progressive levels, with every level featuring at least one statement requiring respondent endorsement. Respondents' agreement was measured using a 5-point or a 2-point response scale. The study population comprised all university staff (lecturers and administrators); utilizing simple random sampling, and 157 valid responses were collected. The findings revealed that the People indicator scored Level 2 (60.6%) and the Process indicator also at Level 2 (65.2%), while the Technology indicator demonstrated a significantly higher maturity at Level 5 (70.5%). This indicates that the maturity of both the People and Process dimensions remains comparatively low relative to Technology. Consequently, strategic interventions are essential to enhance these indicators, thereby contributing to the improved management and development of distance education institutions.